Analisis Faktor-Faktor yang Mempengaruhi Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2013-2018 - Miftakhul Jannah (Journal of Economic, Management and Entrepreneurship, 2023)
The purpose of this research is to examine the factors that influence company value. The type of research used is quantitative research in explanatory format. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange for the 2013-2018 period. The sampling technique was carried out using the purposive sampling method. The exogenous variables in this research are ownership structure which is proxied by managerial ownership and institutional ownership as well as investment opportunity set which is proxied by market value book equity (mvebve). Meanwhile, the endogenous variable in this research is company value which is proxied by Price Book Value. This research uses secondary data in the form of financial reports and statistical data for manufacturing companies for the 2013-2018 period. The data analysis technique used is multiple regression analysis with SPSS 21 software. The results of this research show that: (1) managerial ownership has no significant effect on company value; (2) institutional ownership has no significant effect on firm value; and (3) investment opportunity set has a significant effect on company value.